2023
DOI: 10.1108/ci-09-2022-0229
|View full text |Cite
|
Sign up to set email alerts
|

Identifying critical challenges to lean construction adoption

Abstract: Purpose This study aims to set out to identify and evaluate potential obstacles to successfully implementing lean construction (LC) as a result. Design/methodology/approach Several indicators were recognized as major obstacles following an exhaustive assessment of the literature and a multicriteria decision analysis based on the analytic hierarchy process (AHP) of information obtained from a questionnaire survey that was directed to practitioners in the Indian construction industry. Findings The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…The results challenge the misconception that LC practices result in additional costs. Instead, it is observed that lean practices prevent cost overruns by saving expenses related to defect correction, reworks, and non-value-adding activities [2,19,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results challenge the misconception that LC practices result in additional costs. Instead, it is observed that lean practices prevent cost overruns by saving expenses related to defect correction, reworks, and non-value-adding activities [2,19,64].…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous reports citing significant benefits from implementing Lean Construction (LC) principles, its adoption rate remains relatively low, with many firms hesitating to implement LC practices [12][13][14]. Lack of awareness has been identified as one of the top barriers to LC adoption by many researchers [15][16][17][18][19]. Similarly, fear of failure or uncertainty associated with LC has prevented the construction industry from embracing Lean practices [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The business prioritizes growing its market share and profitability (Kumar et al, 2018;Mittal et al, 2021aMittal et al, , 2023aSingh et al, 2023). The organizations therefore are concerned about the quality of their products, customer satisfaction, continuous improvement, and manufacturing costs (Mittal et al, 2021b(Mittal et al, , 2023bVerma et al, 2023;Vadivel et al, 2023).…”
Section: Introductionmentioning
confidence: 99%